Quality of life and treatment in the climacteric - Monterrosa Castro, Alvaro (2015)
Quality of life in menopause. Osteopenia: calcium supplementation is necessary ?. Phytoestrogens: current evidence. Nonhormonal pharmacological management of menopause. Hormone replacement therapy: metabolic problems.